Next-Generation Biomarkers: Integration of Multi-Omics Approaches in Clinical Chemistry for Early Disease Detection - Hamid Musa, Nuhad Salam; Jaayoul Burhan, Zainab Khalid; Mohammad Ali, Mohammad Abdul-Mohaimin; Hussein Askar, Hussein Mohammed; AbedRasol Kamil, Ibrahim Yaareb (American Journal of Biomedicine and Pharmacy, 2025)
Biomarkers are molecules used as indicators of normal or pathological processes, or of pharmacological responses to therapy. Omics-based biomarker discovery is rapidly evolving. Next-generation multi-omics approaches are expected to fuel validation kits that will be marketable in precision diagnostics. Clinical chemists will be empowered to develop universal kits that incorporate clinically validated biomarkers from any omics realm, enabling screening for early onset of multiple and unrelated non-communicable diseases using small volumes of body fluids. Early clinical disease detection, through therapeutic or nutritional intervention, reduces mortality, treatment cost, and drug resistance. Multivariate biomarker panels provide higher sensitivity (clinically acceptable if >85%) and specificity (>90%) than single markers (acceptable when >80%), with the combined response displayed through probability scores. A set of safest algorithms can deliver assay results and disease probability during the patient’s clinic visit, increasing practitioner confidence, while the occurrence of any marker above the reference value should trigger patient-directed digital advice. Patient empowerment through digital engagement is required, with practice recommendations from both digital systems and physicians following, in chain with current best clinical practice.